Kepemilikan Manajerial, Kebijakan Pembayaran Dividen dan Efek Moderasi Penurunan Tarif PPh Dividen WPOP Dalam Negeri - Ninik Zulaikah; Mienati Somya Lasmana (Jurnal Akuntansi dan Keuangan, 2013)
This study aims to examine the moderating effect of reduction of dividend income tax rate for domestic individual taxpayers toward managerial ownership and dividend payout policies on companies listed in Indonesia Stock Exchange. The company surveyed a total of 88 companies are companies that pay dividends at least once a year consecutively from 2007 until 2009, and no stock ownership by management. The results show a positive and significant effect of managerial ownership to the company's dividend policy and dividend income tax rate for domestic personal taxpayers moderate the effect of managerial ownership on the increase in dividend payout policy.